THE RELATIONSHIP BETWEEN INTEREST TO LEARN AND LEARNING ENVIRONMENT AT HOME WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII - Randi Makruf Nugraha; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2020)
Student learning outcomes are related to many factors. Interest to Learn and learning environment at home. This study aims to determine the presence or the lack of a positive and significant relationship among the Interest to Learn And learning environment at home with mathematics learning outcomes for students of class VIII First Semester of Islamic Junior High School (Mts) Al - Mu'min Muhammadiyah Tembarak Teamanggung Regency 2019/2020 Academic Year. This study's population are all the students of class VIII First Semester of Mts Al - Mu'min Muhammadiyah Tembarak Teamanggung Regency 2019/2020 Academic Year, consisting of 2 classes with some 36 students. Trial classes and sample classes are taken by random sampling technique and regular Class VIII II and Class VIII I trial. The data collection technique is carried out by using the test and questionnaire method. The test method is used to collect data on student mathematics learning outcomes. In contrast, the questionnaire method is used to collect data on the Interest to learn and the learning environment at home with a mathematics learning outcome. The instrument test uses a validity test, a different power test, and a reliability test. Analysis prerequisite tests are a normality test, independent test, and linearity test. Data analysis for hypothesis testing uses correlation analysis and linear regression analysis. The results showed a positive and significant impact among the Interest to learn and learning environment at home with mathematics learning outcomes. The multiple correlation coefficient (R) of and the coefficient of determination (R2) of with a linear regression 989 equation.